Comprehensive assessment of T cell receptor β repertoire in Stevens–Johnson syndrome/toxic epidermal necrolysis patients using high-throughput sequencing. (February 2019) - Xiong, Hao; Wang, Lanting; Jiang, Menglin; Chen, Shengan; Yang, Fanping; Zhu, Huizhong; Zhu, Qinyuan; Tang, Chenling; Qin, Shengying; Xing, Qinghe; Luo, Xiaoqun
Highlights: Stevens–Johnson syndrome/toxic epidermal necrolysis patients manifest less TCR repertoire diversity. The TCR repertoire diversity might be associated with the clinical severity of disease. Shared V/J gene utilization exist in the same drug induced Stevens–Johnson syndrome/toxic epidermal necrolysis patients. Abstract: Stevens–Johnson syndrome (SJS) /toxic epidermal necrolysis (TEN) are life-threatening severe cutaneous adverse drug reactions characterized by widespread epidermal necrosis. Recent studies have indicated that SJS/TEN is a specific immune reaction regulated by T cells. Certain drug serves as foreign antigens that are presented by major histocompatibility complex (MHC) and recognized by T cell receptors (TCRs), inducing adaptive immune responses. However, few studies have performed detailed characterization of TCR repertoire in SJS/TEN, and it remains unclear whether the particular types of TCRs expanded clonally are drug-specific, which would provide a potential underlying mechanism of SJS/TEN. In this study, using high-throughput sequencing, we comprehensively assessed the diversity, composition and molecular characteristics of the TCRβ repertoires in 17 SJS/TEN patients associated with three different causative drugs including methazolamide (MZ), carbamazepine (CBZ) and allopurinol (ALP). Systematic analysis of the TCRβ sequences revealed that SJS/TEN patients had more highly expanded clones and less TCR repertoire diversity, and the TCR repertoire diversity of these patients showed certain associations with the clinical severity of disease. Similar predominant clonotypes, shared-usage TRBV/TRBJ subtypes and combinations thereof were observed among different subjects with the same causative agent. Our observations provide enhanced understanding of the role of T lymphocytes in the pathogenesis of SJS/TEN and enumerate potential therapeutic targets.